De-Extinction, Regulation and Nature Conservation. (8th July 2020) - Allen, Jessica; Doyle, David M; McCorristine, Shane; McMahon, Aisling
Abstract: This analysis maps the key challenges posed by de-extinction to nature conservation law. The aim is to start a conversation about how such challenges should be framed and addressed if ongoing de-extinction projects in the United States of America (US) and the European Union (EU), the two jurisdictions examined, are successful. The analysis commences by providing a brief overview of existing debates in the conservation literature on the legal and ethical issues posed by de-extinction within the animal context. The article then proceeds to highlight two challenges animals created via de-extinction (de-extinctees) will likely pose for nature conservation law, namely: (1) to what extent taxonomies or definitions of 'species', and the methods for classifying these species under existing conservation frameworks, will be challenged by de-extinction; and (2) how existing conservation law frameworks in the US and the EU would likely apply to de-extinctees, and whether de-extinctees would be protected under these frameworks. It concludes by posing the broader question of whether and to what extent the law should facilitate de-extinction attempts in the same way that it has done for nature conservation.